Effects of hyoscine-n-butylbromide on postoperative nausea and vomiting and postoperative pain in ureteroscopic procedures - Suheyla Abitagaoglu; Ceren Koksal; Cansu Ofluoglu; Caglar Yildirim; Dilek Erdogan Ari (Medicine Science, 2020)
One of the most common complications of anesthesia is postoperative nausea and vomiting (PONV). It is known that, in addition to the use of inhalational anesthetics and opioids, flank pain due to stones and the procedure also plays a role in the development of PONV in patients who undergo ureteroscopy. The purpose of this study was to retrospectively investigate PONV incidence and postoperative pain in patients who were administered hyoscine-N-butyl bromide (HBB) during ureteroscopy. Data from 40 patients who underwent ureteroscopy and were intravenously administered HBB for analgesia were retrospectively evaluated. Demographic data of the patients, PONV incidence and severity of pain at postoperative 15th and 30th min and postoperative 3rd, 6th, 12th, and 24th h were investigated. Additional analgesic requirements were recorded. Ten females (25%) and 30 males (75%) were included in the study. The mean age of the patients was 47.9 ± 14.9 years. Fourteen patients (35%) had comorbidities. Six patients (15.8%) had PONV at postoperative 15th min, two patients (5.3%) had PONV at postoperative 30th min, and one patient (2.5%) had PONV at postoperative 3, 6, 12, and 24th h. The mean VAS scores during the follow-up period were 0.67 ± 1.03, 0.41 ± 0.70, 0.65 ± 1.27, 0.63 ± 1.51, 0.60 ± 1.83, and 0.16 ± 0.60, respectively. Even though PONV is an important problem after ureteroscopy procedures, HBB that is an anticholinergic drug seems to exhibit effective antiemetic properties in addition to providing postoperative analgesic properties in patients who underwent ureteroscopy. [Med-Science 2020; 9(2.000): 482-4]